RETRACTED: The Effect of Communication, Work Stress, and Work Environment on Employee Performance at Ichsan Medical Centre Hospital South Tangerang - Fachri Huzaini Ramadhan; Ahmad Cik; Kumba Digdowiseiso (Syntax Corporation Indonesia, 2024)
This study aims to analyze the effect of communication, work stress, and work environment on employee performance at Ichsan Medical Center Hospital, South Tangerang. The sample in this study was 120 respondents based on the Yamane formula. This study uses primary data with data collection methods through the distribution of questionnaires to 120 respondents. The data analysis technique used inferential analysis with multiple linear regression. The results obtained in this study are communication has a positive effect on employee performance, job stress has a positive effect on employee performance, and the work environment has a positive effect on employee performance. Therefore, Ichsan Medical Center Hospital South Tangerang must provide a better impact so that communication, work stress and the work environment can be maintained at a stable level.